1995
DOI: 10.1126/science.7761832
|View full text |Cite
|
Sign up to set email alerts
|

A Region of Adenylyl Cyclase 2 Critical for Regulation by G Protein βγ Subunits

Abstract: Receptor-mediated activation of heterotrimeric guanine nucleotide-binding proteins (G proteins) results in the dissociation of alpha from beta gamma subunits, thereby allowing both to regulate effectors. Little is known about the regions of effectors required for recognition of G beta gamma. A peptide encoding residues 956 to 982 of adenylyl cyclase 2 specifically blocked G beta gamma stimulation of adenylyl cyclase 2, phospholipase C-beta 3, potassium channels, and beta-adrenergic receptor kinase as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
184
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(191 citation statements)
references
References 33 publications
6
184
1
Order By: Relevance
“…Noticeably, it was recently demonstrated that fl?' subunits of G proteins could bind to a QXXER motif present on several effectors such as adenylyl cyclase 2 and muscarinic potassium channels [28]. This motif is also present in the AID sequence of three neuronal ~ subunits (classes A, B and E) where the arginine residue represents a non-conserved AID amino acid which is absent in the remaining (z~ subunits (classes S~ C and D).…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, it was recently demonstrated that fl?' subunits of G proteins could bind to a QXXER motif present on several effectors such as adenylyl cyclase 2 and muscarinic potassium channels [28]. This motif is also present in the AID sequence of three neuronal ~ subunits (classes A, B and E) where the arginine residue represents a non-conserved AID amino acid which is absent in the remaining (z~ subunits (classes S~ C and D).…”
Section: Discussionmentioning
confidence: 99%
“…AC2 assays have been described (6). When required the peptides were mixed with adenylyl cyclase containing membranes and held on ice for 10 min prior to assays.…”
Section: Methodsmentioning
confidence: 99%
“…AC2 was expressed in Sf9 cells by infection with recombinant baculovirus (10). AC2 assays have been described (6). Bovine AC1 (11) was epitope tagged at the N terminus with the FLAG epitope (10) and expressed in Sf9 cells by baculovirus infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A consensus sequence (QXXER) has been proposed to be involved in the interaction of G␤␥ subunits with adenylyl cyclase type 2, inwardly rectifying K ϩ channels, and phospholipase C␤ (15). A related consensus sequence is within or adjacent to the region of the COOH terminus of inwardly rectifying K ϩ channels which is implicated in binding and regulation by G␤␥ subunits (16,17).…”
mentioning
confidence: 99%